Planning and Project of Medium Voltage Electric Power Distribution Systems - Carnelossi Cunha, Vinicius [UNESP]; Sanches Mantovani, Jose Roberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents a solution strategy for planning and project distribution system problems. This model applies concepts of Tabu Search (TS) metaheuristic to provide a complete solution for the problem, from distribution substations to individual consumers, making it able to be implemented by distribution companies. A 50-bus network was used to evaluate this method that obtained feasible and good solutions for planning and project distribution systems.
Keywords: Electric Power Distribution Systems; Planning and Project; Tabu Search